Investigating offenders’ post-release financial intentions - Mielitz, Katherine Suzanne (Kansas State University, 2018)
Crimes are committed for a vast and varying number of reasons. Many of those who commit crime are found guilty and serve their sentences. In most situations, the offenders will complete their sentences and subsequently be released back into society. The question then arises, is the offender prepared to return to society? There are numerous factors associated with successful reentry, but one that has not yet been addressed is financial behavior after release. This dissertation takes a first step toward understanding potential post-release financial behavior. The purpose of this primary data study was to use the theory of planned behavior as a context to examine how aspects of incarceration history—the type of crime committed (financial and non-financial), total years incarcerated, and total number of convictions—may influence financial attitude, financial subjective norms, perceptions of behavioral control, and post-release financial intentions. Use of the theory of planned behavior in this special, vulnerable population is needed to assist educators and professionals to determine what training offenders may need to succeed once back in society. This study focuses on Georgia Transitional Center participants’ post-release financial intentions. There is not much research regarding men and women who have experienced incarceration and their relationships with financial resources. Understanding the nature of Americans’ financial resources is challenging. Adding incarceration to the equation further complicates the investigation, but it is a worthwhile for a more comprehensive understanding of factors that may later affect success in society. This dissertation is the first study to investigate post-release financial intentions of men and women in a work release program.
Keywords: Financial intentions; Theory of planned behavior; Incarcerated; Reentry; Crime; Financial management